METHODS OF INCREASING TECHNICAL TRAINING OF YOUNG PLAYERS - UMAROV ABBOS ASHUROVICH; KOMRON RASHIDOV KAMOLIDDINOVICH (International Journal of Innovations in Engineering Research and Technology, 2021)
The article analyzes the technical and tactical methods and actions taught to young players, discusses the process of their training and the components of the training load.